Pendampingan Desain Kemasan Produk Kacang Tanah Barandang untuk UMKM di Nagari Tigo Balai - Delvi Yanti; Aninda Tifani Puari; Fadli Irsyad; Eri Stiyanto (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Andalas, 2024)
When comparing Lawang to Nagari Tigo Balai, the latter exhibits an attractive appearance on product packaging, which is one of the crucial factors in the marketing strategy of micro, small, and medium enterprises (UMKM). UMKM's issues in the Nagari Tigo Balai area include limited technology and knowledge in redesigning packaging. This Community Service Activity (PKM) aims to assist UMKM in Nagari Tigo Balai in designing packaging for